Animal as Bioindicator of River Water Quality: Bibliometric Analysis - Hery Fajeriadi; Nurul Aulia; Ulya Ruwaida; Rina Oktaviana; Zevira Fransisca Aurora; Opik Prasetyo (Journal of Bioresources and Environmental Sciences, 2025)
River water quality is vital to life, but anthropogenic activities have caused significant degradation, threatening aquatic ecosystems and clean water supplies. Although bioindicators have long been used to monitor river health, there has been no bibliometric review to analyze trends and research gaps in this field. Previous studies have mostly focused on specific species or physical-chemical parameters, but have not yet fully integrated an ecosystem indicator approach. Therefore, this study aims to address this gap by conducting a bibliometric analysis of publications on animals as bioindicators of river water quality. The method used is a bibliometric review using data from the Scopus database (2020–2024), analyzed using VOSviewer to visualize the co-occurrence of keywords, as well as a descriptive analysis of publication trends, journals, and fields of study. The results show a significant increase in publications since 2020, with Ecological Indicators and Science of the Total Environment as the leading journals, and Environmental Science as the dominant field of study. Co-occurrence analysis identified three main research clusters: ecology and communities, physiological responses to pollutants, and heavy metal contamination. These findings indicate that global research focus is concentrated on the impact of heavy metal pollutants, while the issues of microplastics and climate change on bioindicators are relatively less explored. This clustering pattern also emphasizes the importance of combining ecological, physiological, and pollution-related approaches, reflecting interdisciplinary advances in this area. In conclusion, the use of animals as bioindicators has a strong theoretical basis and offers an integrated approach to water management such as river. Future studies focusing on developing more sensitive bioassay methods and conducting long-term toxicity analyses are important, but they must also incorporate molecular tools such as eDNA and metabolomics to strengthen biomonitoring systems. In addition, decision makers are encouraged to implement bioindicators that use animals in water quality monitoring systems in order to improve early detection capabilities for river ecosystem degradation.